Interactive flow behaviour and heat transfer enhancement in a microchannel with cross flow synthetic jet - Jagannatha, Deepak; Chandratilleke, Tilak; Narayanaswamy, Ramesh (Multi-Science Publishing, 2010)
This paper examines the effectiveness in combining a pulsating fluid jet for thermal enhancement in microchannel heat sinks. The proposed arrangement utilises an oscillating diaphragm to induce a high-frequency periodic fluid jet with zero net mass output at the jet orifice hence, termed "synthetic jet". The pulsed jet interacts with the fluid flow through microchannel passages altering their flow characteristics. The present study develops a 2-dimensional finite volume numerical simulation based on unsteady Reynolds-averaged Navier-Stokes equations for examining the microchannel-synthetic jet flow interaction. For a range of parametric conditions, the behaviour of this periodic flow with its special features is identified and the associated convective heat transfer rates are predicted. The results indicate that the pulsating jet leads to outstanding thermal performance in microchannel flow increasing its heat dissipation rate by about 4.3 times compared to a microchannel without jet interaction within the tested parametric range. The degree of thermal enhancement is seen to grow continuously to reach a steady value in the absence of fluid compressibility. The proposed strategy has an intrinsic ability for outstanding thermal characteristics without causing pressure drop increases in microchannel fluid passages, which is identified as a unique feature of the technique.The study also examines and presents the effects of fluid compressibility on the heat removal capacity of this arrangement. The technique is envisaged to have application potential in miniature electronic devices where localised cooling is desired over a base heat dissipation load.